Teacher’s Strategies In Assisting Learning Disability Students In Inclusive Classroom of SDN 3 Karangrejo Banyuwangi - Maryam Faizah; Ikrima Nurul Maulidah (IAI Al Khoziny Buduran Sidoarjo, 2020)
The high number of students with learning disability in Banyuwangi Regency requires teachers to implement appropriate strategies in the learning process. Learning disability can be interpreted as a condition in the learning process which characterized by obstacles that are realized or not by people who experience in psychological, sociological, or physiological in the whole learning process that interfere the listening, speaking, reading, writing, and counting. The purposes of this study are: (1) Determine the application of teacher strategies who have learning disability in SDN 3 Karangrejo Banyuwangi. (2) Understand the factors support and inhibit teacher strategies in helping students’disability. The method applied is a descriptive qualitative approach. The results showed that, (1) The strategies implemented by teachers are applying cooperative learning models so that students who have learning disability can work together with other students, implementing classes with a pull out system which means students who have learning disability can learn with the teacher at a certain time by using several learning media (2) Supporting factors of teacher strategies are supported by parents and the existence of private tutor. While the factors inhibiting are students' mood swings and inadequate school facilities.